Role of feedback and motivational climate in promoting exercise among children - Ang, Eugene Kian Boon (2014)
With childhood obesity as a growing concern in Singapore, parents, educators and policymakers are finding new ways to encourage children to be more physically active. This study focuses on using communicative components in a digitally-mediated environment (through digitally assisted physical gaming, or exergaming) as an intervention method to promote leisure time physical activity and encourage exercise behaviour. While past research explored various factors that impact the effectiveness of a health intervention programme, this research taps on the self-determination theory and other behavioural theories to investigate communication components that are most salient in an intervention programme involving exergaming – feedback type and motivational climate. A 2 (peer or authority) X 2 (self-improvement or social-comparative) between-subject factorial design was used. The intervention was held as a 1.5-day exergaming camp consisting of 10.5 hours of activity for 216 students aged 9 to 12. They were split into respective treatment conditions and participated in nutrition and exercise-related activities through the XBOX360 Kinect and mobile applications on the iPod Touch. They had to either set their own target scores (self-improvement feedback) or compete against their teammates (social-comparative feedback), and received motivational notes from either their teammates (peer-based motivational climate) or facilitators (authority-based motivational climate). Results from this study provide valuable insights into tailoring child-specific interventions. Findings suggest that self-improvement feedback is more effective than social-comparative feedback in influencing intention to exercise, and this effect is further enhanced in a peer motivational climate. It was also found that attitude towards exercise was a significant predictor of behavioural intention in a physical activity context. Theoretical implications and recommendations for parents, educators and health authorities are discussed.